Pengaruh Likuiditas, Leverage, Kebijakan Dividen, Ukuran Perusahaan, Good Corporate Governance dan Sales Growth Terhadap Nilai Perusahaan - Herdiani, Nita Putri; Badina, Tenny; Rosiana, Rita (Jurusan Akuntansi Politeknik Negeri Padang, 2021)
This study was conducted to determine the effect of liquidity, leverage, dividend policy, firm size, good corporate governance, and sales growth on firm value in manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2016 – 2020 period. Listed on the Indonesian Sharia Stock Index (ISSI) with a study period of 5 years. The sample selection method was purposive sampling and obtained 29 companies that matched the sample criteria. The data analysis method uses panel data and ordinary least square (OLS). The results of hypothesis testing show that partially liquidity has a negative and significant effect on firm value, leverage has a negative and significant effect on firm value, dividend policy has a positive and significant effect on firm value, firm size has a positive and significant effect on firm value, board of commissioners size has a negative and significant effect on firm value, audit committee size has a negative and significant effect on firm value, and sales growth has a negative and significant effect on firm value. Simultaneously there is a significant influence of liquidity, leverage, dividend policy, firm size, board of commissioners size, audit committee size, and sales growth on firm value.